The Influence of Work-Life Balance and Organizational Culture on Employee Performance at PT. Hi-Lex Cirebon - Tasyana; Rahma, Indah Athifa; Syahroni, Bachrudin; Moh. Yudi Mahadianto (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research explores the impact of work-life balance and organizational culture on employee performance at PT. Hi-Lex Cirebon. The study is driven by ongoing challenges in the manufacturing industry, where employees are frequently subjected to intense workloads and extended working hours, which may disrupt the equilibrium between their professional and personal lives. Additionally, a workplace culture that lacks support can diminish motivation and reduce productivity. As such, this research investigates the combined effect of work-life balance and organizational culture on job performance. Utilizing a quantitative method with an explanatory research design, the study applies Structural Equation Modeling (SEM) through Partial Least Squares (PLS) for data analysis. The results indicate that both work-life balance and organizational culture contribute positively and significantly to employee performance. These findings underscore the necessity for organizations to cultivate a work environment that supports both personal and professional well-being while reinforcing strong cultural values to boost employee performance and satisfaction.